Imaging findings in spinal sarcoidosis: a report of 18 cases and review of the current literature. Issue 1 (February 2019) - Soni, Neetu; Bathla, Girish; Pillenahalli Maheshwarappa, Ravishankar
Purpose: Spinal sarcoidosis, referring to involvement of the spine in sarcoidosis, is relatively rare and may mimic other neurological disease affecting the spine. The authors present a clinic radiological review of 18 spinal sarcoidosis patients who presented to a tertiary hospital, with emphasis on initial imaging and radiological response to treatment. Materials and methods: We retrospectively reviewed our departmental imaging archives over a 15-year period and found 49 cases of neurosarcoidosis out of which 18 patients had spinal magnetic resonance imaging. Results: Approximately 72% (13/18) of the neurosarcoidosis patients showed some form of spinal involvement. The clinical, epidemiological and imaging data were reviewed for these 13 patients at presentation and follow-up. The findings on magnetic resonance imaging included leptomeningeal enhancement (61%), pachymeningeal (23%), intramedullary enhancing lesions (38%) and bony involvement (15%). The cervical segment was most frequently involved followed by the thoracic segment. Involvement was often long segment (4.2 spinal segments) with proclivity for the dorsal cord. Mean follow-up was 23.2 months. A complete or near-complete radiological response occurred in 66% while partial response was seen in 25% patients. Four patients had isolated central nervous system involvement including one with isolated spinal cord involvement. On diffusion-weighted imaging, the apparent diffusion coefficient of intramedullary lesions was increased compared to normal-appearing cord on baseline and subsequent follow-up scans. Conclusions: Spinal sarcoidosis was previously considered uncommon but is being increasingly recognized with widespread use of magnetic resonance imaging. Proclivity for dorsal surface involvement is characteristic, although not necessarily pathognomonic. Also, quantitative diffusion studies may serve as a biomarker for the disease activity and parenchymal injury.